Perbuatan Melawan Hukum dalam Kebocoran Data Penumpang Lion Air Group - Nuzulia Kumala Sari; Edi Wahjuni; Afiif Hadiani Pratiwi (Journal of Private and Economic Law, 2021)
ABSTRACT: Nowadays, data that contains the content of privacy matters has become a valuable commodity that is often associated with effective instruments for identifying a person. The case of Lion Air Group passenger data leakage in online forums that has harmed passengers as consumers is contained in Article 36(1) of the Regulation of the Minister of Communication and Information Technology of the Republic of Indonesia Number 20 of 2016 concerning Personal Data Protection in Electronic Systems is only subject to administrative sanctions in the form of oral warnings, written warnings, temporary suspension of activities, and announcements on online sites. The absence of steps taken by Lion Air Group to provide certainty or matters that are compensatory to the consumer makes the rights of consumers are not fulfilled. This paper uses the doctrinal method in dealing with problems relating to unlawful acts committed by two former GoQUo employees as Malindo Air's partners in online flight ticket booking service providers in the leakage of Lion Air Group passenger data. The results of the discussion showed that accessing and stealing other people's personal data as well as spreading information that contains other people's personal data without rights is an illegal act that causes liability in the form of compensation. Losses suffered by consumers both materially and immaterially can be resolved through non-litigation and litigation channels.